2012
DOI: 10.1007/s10875-012-9810-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-27, Th1 and Th17 in Patients with Aplastic Anemia

Abstract: The upregulation of IL-27 might cause Th1 differentiation and immune disorders in AA patients. Blocking the expression of IL-27 could therefore be a reasonable therapeutic strategy for AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Previous studies reported that CD4 + Th17‐cells immune responses play an important role in the pathogenesis of AA. The increased expressions of IL‐17 mRNA and intracellular IL‐17 in BM and PB mononuclear cells have been observed in patients with AA . Although Feng et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that CD4 + Th17‐cells immune responses play an important role in the pathogenesis of AA. The increased expressions of IL‐17 mRNA and intracellular IL‐17 in BM and PB mononuclear cells have been observed in patients with AA . Although Feng et al.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expressions of IL-17 mRNA and intracellular IL-17 in BM and PB mononuclear cells have been observed in patients with AA. [15][16][17] Although Feng et al measured 31 plasma cytokines using an immunobead-based multiplex assay in patients with AA and MDS, the level of IL-17 was undetectable. [4] Conversely, using a human ELISA kit, Gu et al demonstrated elevated IL-17 levels in BM and PB plasma of patients with AA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple reports have shown basal levels of circulating IL-27p28 in humans; these levels are altered in many disease states, including bacterial infections, sepsis, aplastic anemia, and ankylosing spondylitis (167)(168)(169)(170)(171). The interpretation of what the changes in levels of IL-27 mean is not straightforward; increased production could indicate causality or simply be a secondary host response to ongoing disease.…”
Section: Translational Implications Of Il-27mentioning
confidence: 99%